Studies on the absorption of volatile fatty acids in calves : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Nutrition at Massey University of Manawatu - Khouri, Ramsay Hanna (Massey University, 1966)
Ruminants subsist on fibrous plant feeds not normally consumed by man. They transform inedible and undigestible plant material into palatable and digestible human food. Their meat and milk are rich sources of essential amino-acids, vitamins and minerals. These foods are natural supplements to the human diet which is predominantly of plant origin. Interest in the nutrition and digestive physiology of ruminants has resulted in the accumulation of a voluminous literature which has been reviewed by Annison and Lewis (1959), Barnett and Reid (1961), Blaxter (1962) and Kay and Hobson (1963). This interest has also prompted two recent international symposia, the proceedings of which have been edited by Lewis (1961), and Dougherty, Allen, Burroughs, Jacobson and McGilliard (1965). Mature ruminants are assumed to have the same basic nutritional requirements for energy, amino-acids, vitamins, minerals and water as do the simple-stomached animals. Their digestive juices, like those of all other mammals, do not contain any cellulases. An extensive microbial population, located largely within the rumen, and to a lesser extent in the caecum and colon, enables them to thrive on fibrous plant feeds that are frequently deficient in some of the essential amino-acids and water-soluble vitamins.
Keywords: Ruminant nutrition; Rumen microbiology; Calf physiology